2009
DOI: 10.1016/j.jus.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive uropathy and acute renal failure due to ureteral calculus in renal graft: a case report

Abstract: Introduction: Obstructive uropathy caused by kidney stones is quite rare in transplant kidneys. Clinical case: The authors report the case of a patient, previously gastrectomized for gastric carcinoma. He underwent renal transplantation using uretero-ureterostomy, and presented an episode of acute renal failure 7 years after surgery. Ultrasound (US) examination showed no sign of rejection but allowed detection of moderate hydronephrosis in the transplant kidney. Subsequent computed tomography (CT) revealed a k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…As in general patient populations, kidney stones can also cause acute kidney injury in kidney transplant recipients[49-52]. Since kidney transplant recipients can have obstructed kidney stones without any symptom of pain[26,28], prompt diagnosis and the removal of obstructed stones are the keys to preventing renal allograft failure[18].…”
Section: Resultsmentioning
confidence: 99%
“…As in general patient populations, kidney stones can also cause acute kidney injury in kidney transplant recipients[49-52]. Since kidney transplant recipients can have obstructed kidney stones without any symptom of pain[26,28], prompt diagnosis and the removal of obstructed stones are the keys to preventing renal allograft failure[18].…”
Section: Resultsmentioning
confidence: 99%
“…It is thus surprising that evidence is limited linking kidney stones to graft function and survival after kidney transplantation. A small number of case reports have been published illustrating cases of obstructive nephropathy and kidney graft failure due to renal or ureteral calculi [ 69–71 ]. A single-centre retrospective observational study conducted in 574 kidney transplant recipients, with a mean (±standard deviation) follow-up period of 55 ± 53 months and nephrolithiasis prevalence of 4.4%, demonstrated that nephrolithiasis did not have an impact on allograft survival (odds ratio 1.04, CI 0.708–1.54, P = .824) [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of proximal ureteric calculi can be reliably made on ultrasonography while mid and distal ureteric calculi are more effectively detected using CT or MR urography. 13 Management of calculi in transplanted kidney is similar to the management in patients with solitary functioning kidneys. The minimally invasive techniques are performed first.…”
Section: Discussionmentioning
confidence: 99%